Cana-de-açúcar in natura ou hidrolisada com óxido de cálcio para equinos adultos estabulados - Renata Vitarele Gimenes Pereira (2014)
During the dry season the sugar cane is widely used in the diet of horses. However, it is used without criteria, with little research to evaluate its use in the diet of this species. The objective of this study was to evaluate the use of in natura or hydrolyzed sugar cane with calcium oxide (CaO) stored for up to three days, in the diet of adult stabled horses. For this purpose, six experiments were performed, the first being the sole evaluation of in natura or hydrolyzed sugar cane mised with CaO (0 , 0.5, 0.75 and 1%) and stored for 96 hours by means of temperature, pH, degree brix and nutritional value . The remaining experiments evaluated mongrel castrated adult horses (n = 16), aged six to 13 years, weighing 372-407 pounds and kept in individual stalls. The roughage was sugar cane and for balancing the Ca: P ratio and PB : ED, the animals were supplemented with 1 kg of wheat bran and 1 kg of soybean meal. The selected animals were clinically healthy and presented with no history of abnormal digestive tract. Intake, digestibility, behavior, blood count, serum biochemistry, clinical parameters, fecal characteristics and gastroscopy of animals fed for thirty days with cane sugar bite 1 to 2cm fresh or hydrolyzed with 0.5% CaO as fed and stored for 24, 48 and 72 hours were evaluated. Under the conditions of temperature and humidity of the present study, the addition of all the concentrations of CaO studied were effective to maintain the nutritional value of sugar cane and allowed little variation in temperature, pH and brix degree, allowing it to be used for up to 96 hours of storage. However, the CaO needs to be added to the sugar cane only when it is intended to store it for more than 24 hours. For the usage in the diet of horses, it is suggested that a dose of 0.5 % CaO be used in sugar cane face to the difficulty of balancing the levels of Ca / P of diet with the addition of higher doses. The intake of dry matter by horses fed with in natura or hydrolyzed sugar cane is according to the recommendations for animal category. The hydrolyzed sugar cane, being stored for 72 hours, rendered greater intake and digestibility of nutrients, thereby improving the nutritional quality of cane to be used as roughage in the diet of horses. Nutrient digestibility of the diet of horses fed with in natura or hydrolyzed sugar cane and the concentrate can be determined by LIPE®. The treatment did not affect leisure time, feeding time and sleeping time of horses. It was not observed the occurrence of any behavior disorder in any treatment during the experimental period. The treatments did not affect the physiological parameters, the physicochemical characteristics of the feces, the blood count or the serum biochemistry of animals. By means of the methods employed and the period of study, no negative effect of the treatments were observed, either in stomach pH or in the number of gastric ulcers and severity of the existing ones. Although numerically clinical signs of the increasing number and severity of ulcers in the aglandular region have been observed due to the consumption of sugar. More studies in assessing the effects of sugar cane as food for horses in different environmental and provided for more than 30 days conditions are, then, required.